The circadian syndrome is a predictor for cognition impairment in middle‐aged adults: Comparison with the metabolic syndrome - Zumin Shi (287671) (2024)
Aims Circadian syndrome (CircS) is considered a better predictor for cardiovascular disease than the metabolic syndrome (MetS). We aim to examine the associations between CircS and MetS with cognition in Chinese adults. Method We used the data of 8546 Chinese adults aged ≥40 years from the 2011 China Health and Retirement Longitudinal Study. MetS was defined using harmonised criteria. CircS included the components of MetS plus short sleep and depression. The cut‐off for CircS was set as ≥4. Global cognitive function was assessed during the face‐to‐face interview. Results CircS and MetS had opposite associations with the global cognition score and self‐reported poor memory. Compared with individuals without the CircS and MetS, the regression coefficients (95%CI) for global cognition score were −1.02 (−1.71 to −0.34) for CircS alone and 0.52 (0.09 to 0.96) for MetS alone in men; −1.36 (−2.00 to −0.72) for CircS alone and 0.60 (0.15 to 1.06) for MetS alone in women. Having CircS alone was 2.53 times more likely to report poor memory in men (95%CI 1.80–3.55) and 2.08 times more likely in women (95%CI 1.54–2.81). In contrast, having MetS alone was less likely to report poor memory (OR 0.64 (0.49–0.84) in men and 0.65 (0.52–0.81) in women). People with CircS and MetS combined were more likely to have self‐reported poor memory. Conclusions CircS is a strong and better predictor for cognition impairment than MetS in Chinese middle‐aged adults. MetS without short sleep and depression is associated with better cognition. Other Information Published in: Diabetes/Metabolism Research and Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/dmrr.3827